MAGNETIZATION AND MAGNETIC SUSCEPTIBILITY OF JADEITE - Bartkowska J.A.; Cisowski J.; Mazurak Z.; Voiron J.; Heimann J.; Czaja M. (My University, 2004)
We have studied the high-field magnetization (up to 14.5 T) and magnetic susceptibility in the temperature range 1.7 -420 K of two samples of jadeite (NaAlSi2O6), white and green, containing transition metal ions and originating from Burma (now Myanmar). It appears that the high-temperature susceptibility data obey the Curie-Weiss law indicating the onset of the antiferromagnetic interaction between the magnetic ions. This interaction is also seen in the high-field magnetization data which are well described by the phenomenological cluster model. As a result of our analysis, we have identified the Fe3+ ions as the dominant ones in the studied jadeites and we have determined the molar concentration of these ions (0.8% in white- and 2.5% in greenjadeite) as well as the diamagnetic susceptibility of the jadeite matrix (-3.8 x 10(-7) emu/g).
Keywords: jadeite; magnetization; magnetic susceptibility; magnetic ion concentration